Mucosal immunity: The missing link in comprehending SARS-CoV-2 infection and transmission - Russell, Michael W.; Mestecky, Jiri (Frontiers in Immunology, 2022)
SARS-CoV-2 is primarily an airborne infection of the upper respiratory tract, which on reaching the lungs causes the severe acute respiratory disease, COVID-19. Its first contact with the immune system through the epithelia of the nasal passages and Waldeyer’s ring of tonsils and adenoids induces mucosal immune responses revealed by the production of secretory IgA (SIgA) antibodies in saliva, nasal fluid, tears, and other secretions within 4 days of infection. Evidence is accumulating that these responses might limit the virus to the upper respiratory tract resulting in asymptomatic infection or only mild disease. The injectable systemic vaccines that have been successfully developed to prevent serious disease and its consequences do not induce antibodies in mucosal secretions of naïve subjects, but they may recall SIgA antibody responses in secretions of previously infected subjects, thereby helping to explain enhanced resistance to repeated (breakthrough) infection. While many intranasally administered COVID vaccines have been found to induce potentially protective immune responses in experimental animals such as mice, few have demonstrated similar success in humans. Intranasal vaccines should have advantage over injectable vaccines in inducing SIgA antibodies in upper respiratory and oral secretions that would not only prevent initial acquisition of the virus, but also suppress community spread via aerosols and droplets generated from these secretions.